The duality of presence and absence in the diwan of the insane and obsessive-compulsive patients in the Abbasid era A psychoanalytic study - Raed Okla Kalf , Asst. Prof. Dr. (Wasit Journal for Human Sciences, 2025)
Summary:Objective of the study: This study aims to explore the psychological dimension underlying the duality of presence and absence in the poetry of the insane and obsessive-compulsives in the Abbasid era, through analyzing selected texts representing this category of poets who were known for their severe psychological experiences, and revealing the representations of this duality in their poetic discourse And analyzing its psychological dimension, considering it as a reflection of internal conflicts related to the self and the world, or to the conscious and the unconscious, in addition to clarifying the relationship between this duality and psychological disorders such as anxiety, obsessive-compulsive disorder, depression, and schizophrenia, and shedding light on how to employ this duality as an expressive tool for the poet’s suffering and his confusion between the desire for exposure and the desire for concealment, as well as revealing the connection between the psychological context and the artistic function of this duality.Research Problem: The research problem attempts to answer the following questions:How does the duality of presence and absence manifest itself in the poetry of insane and obsessive-compulsive people during the Abbasid era, and what is its psychological significance in light of literary psychoanalysis? What forms did presence and absence take in poetic texts?.Significance of the study: It contributes to filling a research gap related to the psychological dimension of the duality of presence and absence in the poetry of a group that has rarely received specialized critical attention. It also presents a new approach that blends literary and psychological analysis, which enriches interdisciplinary studies in Arabic literature.
Keywords: presence, absence, madmen, obsessives, Abbasids